My Dad ran over a frog : a Christmas story - Portlock, Rob. (Downers Grove, Ill. : InterVarsity Press, 1992)
On Christmas Eve, a boy brings home to recuperate a frog his father has hit with a car, and it becomes an integral part of the family's Christmas.
Keywords: Christmas -- Fiction; Frogs -- Fiction